I03 Swallowing Function In The Early, Middle And Late Stages Of Huntington's Disease. (17th September 2014) - Dello Monaco, AR; Nuzzi, A; Parente, A; Lavermicocca, V; Chiarelli, T; De Tommaso, M; Fiore, P; Megna, M
Abstract : Background: Swallowing problems are common among people with Huntington's disease (HD). Evidence suggests that death usually results from respiratory complications often caused by dysphagia. However, there are no studies which examine systematically the swallowing function through the successive stages of HD. Aims: The purpose of this study is therefore to investigate the swallowing function and provide appropriate management of oral feeding difficulties in relation to disease progression. Methods: Thirty-eight patients (mean age= 50.62, SD ± 12.7) with genetically confirmed HD underwent swallowing evaluation. Each subject was clinically assessed with the Unified Huntington's Disease Rating Scale (UHDRS) and was classified in one of the three stages of the disease (early, middle and late) according to the guidelines recommendations. Results: In the early stage of HD, swallowing alterations were observed in 11% of the patients and required the application of diet restrictions, compensatory strategies and postures. The prevalence of swallowing impairments at the middle stage of the disease had the same trend as the first stage. Severe dysphagia was mainly represented in the late stage (26%); in fact, the two subjects receiving nutrition through non-oral feeding were in this stage of HD. Conclusions: Although, dysphagia is challenging in the last stage of the neurodegenerative disease, swallowing difficulties occur since the disease onset. The results confirm the importance of ongoing assessment and management of dysphagia in the early stage, as recommended by the EHDN Standards of Care Speech and Language Therapy Working Group, and provide directions to further improve the quality of care delivered to HD patients.